Transcription factor MEF2D regulates aberrant expression of ACSL3 and enhances sorafenib resistance by inhibiting ferroptosis in HCC - Li, Xue; Chen, Shimin; Shi, Yuanyuan; Wang, Yuanjing; Wang, Xuanzhe; Lin, Qian; Wu, Chao; Fang, Wenshuo; Sun, Peng; Ma, Leina (Frontiers in Pharmacology, 2024)
Sorafenib is a first-line treatment for HCC; however, acquired resistance often results in a poor prognosis, indicating a need for more effective therapies. Sorafenib induces cell death through an iron-dependent mechanism known as ferroptosis, which is closely associated with the onset and progression of HCC. In this study, we observed that ACSL3 was aberrantly expressed in HCC and facilitated the progression from NAFLD to HCC. The abnormal expression of ACSL3 inhibited ferroptosis and enhanced sorafenib resistance in HCC. ACSL3-silenced HCC cells treated with specific concentrations of sorafenib exhibited reduced cell viability and increased levels of ferroptosis. The transcription factor MEF2D directly regulated the upregulation of ACSL3 expression. MEF2D bound to the promoter regions of ACSL3 to enhance its transcription and negatively regulate ferroptosis in HCC. In conclusion, our findings demonstrated for the first time that MEF2D regulated the aberrant expression of ACSL3 and enhanced sorafenib resistance by inhibiting ferroptosis in HCC. 1 Ethical Committee of the Medical College of Qingdao University (Animal Ethics Approval Number: QDU-AEC-2022097).Clinical information and surgical specimens were taken patients with NAFLD-related HCC from the